Bloodborne Viral Pathogen Contamination in the Era of Laboratory Automation. (6th January 2020) - Bryan, Andrew; Cook, Linda; Atienza, Ederlyn E; Kuypers, Jane; Cent, Anne; Baird, Geoffrey S; Coombs, Robert W; Jerome, Keith R; Wener, Mark H; Butler-Wu, Susan M
Abstract: BACKGROUND: The CDC states that laboratory testing for persons under investigation for Ebola virus disease can be safely performed using automated laboratory instruments by adhering to bloodborne pathogen practices. We therefore sought to investigate the levels of viral contamination of a total laboratory automation (TLA) system to guide risk mitigation strategies for handling infectious agents. METHODS: Environmental swabs followed by PCR for hepatitis B (HBV) and hepatitis C (HCV) viruses were taken from a chemistry TLA system during routine clinical use and after running a small number of high-titer HCV samples. Control experiments were performed to ensure the recovery of DNA and RNA viruses by swabs from a representative nonporous surface. RESULTS: Of 79 baseline swabs for nucleic acids performed on the TLA system, 10 were positive for HBV and 8 for HCV. Viral nucleic acid was consistently detected from swabs taken from the distal inside surface of the decapper discharge chute, with areas adjacent to the decapper instrument and the centrifuge rotor also positive for HBV or HCV nucleic acid. Contamination was occasionally detected on exposed surfaces in areas without protective barriers between samples and personnel. After running known HCV-positive samples, at least one additional site of contamination was detected on an exposed area of the line. CONCLUSIONS: A low level of viral contamination of automated clinical laboratory equipment occurs in clinical use. Given the risks associated with highly infectious agents, there is a need for risk-mitigation procedures when handling all samples.